DINAMIKA DAN PROBLEMATIKA ASURANSI SYARIAH: Mekanisme Kerja Asuransi Syariah & Prosedur Pembayaran Klaim - Sulistyowati Sulistyowati (El-Qist: Journal of Islamic Economics and Business (JIEB), 2012)
The mechanism of action of sharia insurance is essential to distinguish between Shariah insurance with conventional insurance lies in how the work is done from the premium deposits, investment funds, to the payment of insurance claims to participants stricken or disaster. Everything is summed up in the concept of the working mechanism Shariah insurance. Discussion about the mechanism of action or Shariah insurance, will be divided in two basic discussion in accordance with Shariah insurance payment itself, the family insurance and insurance Shari'ah common. This division is very important to do considering the mechanism of action of these two Shariah suransi it memuliki little difference, namely in the management of premiums paid to insurance companies Shari'ah. Difference arises because "something" that is to be insuranced is different, if in general insurance (loss) the insured's property or the property insurance participants, whereas in family insurance (life) which is self-insured insurance participants themselves. While the claims payment procedure is no difference between a family Takaful and Takaful general. The difference lies in the source of payment of claims. For the payment of claims to family Takaful insurance participants apart from savings and profit sharing of investment is also sourced from the savings tabarru', whereas in the general Takaful is not a savings tabarru' but the pristine source of savings and profit sharing insurance participants, while the payment of claims to do participants at the stricken insurance or out of contract or insurance participants withdrew into Islamic insurance company clients and most importantly Takaful insurance is not the same as conventional.